Hubungan Spiritual Well-Being Dengan Kualitas Hidup Pada Orang Dengan HIV/AIDS - Nessy Anggun Primasari; Muttaqien, Salsabilla; Sandi, Yudisa Diaz Lutfi; Saripah, Eli; Wabula, La Rakhmat; Ardiansyah, Fakrul; Sitanggang, Yohana Agustina (Sekolah Tinggi Ilmu Kesehatan Stella Maris Makassar, 2025)
People diagnosed with HIV will experience stress and emotional distress because they feel that their lives are not what they expected, which will affect all aspects of their lives. Spirituality is believed to have a positive impact and provide strength so that people living with HIV/AIDS (PLWHA) are able to face problems in their lives with positive coping mechanisms. This study aims to determine the relationship between spiritual well-being and quality of life in people living with HIV/AIDS (PLWHA). This study employed a quantitative correlational method with a cross-sectional design conducted at the Pamanukan Community Health Center. Respondents were selected using purposive sampling, resulting in 130 respondents. Data collection was conducted using the Spiritual Well-Being Scale (SWBS) and WHOQOL-HIV BREF questionnaires, which have been validated and proven reliable. The data obtained were analyzed using the Spearman Rank correlation test, yielding significant results (r < 0.001) with a moderate correlation coefficient (r = 0.458) and a positive direction of association. This indicates a relationship between spiritual well-being and quality of life among PLWHA, where higher spiritual well-being is associated with higher quality of life.